A New Device to Monitors New Born Child Health Conditions in an Incubator with Wireless Technology - Kalai Magal, R (International Journal of Computer Sciences and Engineering, 2025)
Nowadays a newborn child as a immature death is increasing due to not proper monitoring in incubator by the people. if automatic control and monitor system is needed for the hospital to avoid the new born child death. The proposed work is design a new device to monitor baby condition and send alert call to parents, nurses and doctors. The arduino based New Born child incubator helps to all peoples, the cost this proposed works very less than today’s New Born child incubator which are used in big hospital. So, everyone which belongs to economical backward also use of it. This proposed work not only used for monitoring and controlling the temperature but also provide number of advantages such as controlling humidity, monitoring weight, detection of sound etc.